Correlation between the serum sodium and the severity of liver disease in cirrhotic patients - Mamun, AA; Mridha, MJU; Alam, K; Asraf, MS; Ferdoushi, S; Majid, F (Bangladesh Medical Journal, 2014)
Though hyponatremia is the common sequel of cirrhotic patient and had impact on the clinical management of cirrhotic patient, no such study had been done yet in Bangladesh, so the present study planned to elucidate the prevalence and to find out any association of hyponatremia and the severity of cirrhosis. The severity was scaled by Child-Pugh score. This study included 85 patient of both sex having mean age of 46.5±11. Hepatitis B virus infection was the main cause of cirrhosis (68%) and 18% cirrhotic patients had attack with hepatitis C virus. The study sought that about 30% of cirrhotic patient had hyponatremia (serum sodium >130 meq/L). We found neither association nor correlation of hyponatremia with Child Pugh score. The study found that serum chloride varied directly with sodium but indirectly with potassium. So we conclude that the hyponatremia was a common manifestation of cirrhosis but the severity of liver disease had no effect on serum electrolytes profile. DOI: http://dx.doi.org/10.3329/bmj.v42i3.18999 Bangladesh Med J. 2013 Sept; 42 (3): 73-77